2014
DOI: 10.1089/neu.2013.3153
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Very-Long-Term Sociocognitive Function after Pediatric Traumatic Brain Injury: Evidence for the Vulnerability of the Immature “Social Brain”

Abstract: Emotion perception (EP) forms an integral part of social communication and is critical to attain developmentally appropriate goals. This skill, which emerges relatively early in development, is driven by increasing connectivity among regions of a distributed sociocognitive neural network and may be vulnerable to disruption from early-childhood traumatic brain injury (TBI). The present study aimed to evaluate the very-long-term effect of childhood TBI on EP, as well as examine the contribution of injury- and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 49 publications
7
78
2
Order By: Relevance
“…While this null finding may be partly attributable to the fact that relatively few participants had CC lesions identifiable on SWI, we speculate that this unexpected result may to some extent reflect the influence of timing of cerebral insult in the present TBI sample. Most interestingly, our results contrast with a recent study that linked corpus callosum injury in infancy and early childhood to very-long-term social cognitive impairment in young adulthood (Ryan, Anderson, et al, 2014). The discrepant findings of these studies may suggest that there is greater likelihood of persisting social dysfunction when brain injuries are sustained during developmental stages that coincide with rapid functional and structural maturation of CC fibres (Beauchamp et al, 2009;Giedd et al, 1996;Luders, Thompson, & Toga, 2010).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While this null finding may be partly attributable to the fact that relatively few participants had CC lesions identifiable on SWI, we speculate that this unexpected result may to some extent reflect the influence of timing of cerebral insult in the present TBI sample. Most interestingly, our results contrast with a recent study that linked corpus callosum injury in infancy and early childhood to very-long-term social cognitive impairment in young adulthood (Ryan, Anderson, et al, 2014). The discrepant findings of these studies may suggest that there is greater likelihood of persisting social dysfunction when brain injuries are sustained during developmental stages that coincide with rapid functional and structural maturation of CC fibres (Beauchamp et al, 2009;Giedd et al, 1996;Luders, Thompson, & Toga, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…The corpus callosum is a common site of injury in pediatric TBI, and damage to this region has been shown to be associated with more diffuse injury (Ewing-Cobbs et al, 2012), poorer long term social cognitive outcomes (Ryan, Anderson, et al, 2014) and poorer parent ratings of social competence (Beauchamp et al, 2009) in samples of children sustaining TBI during the infant and preschool years. Though our findings are broadly consistent with previous research, it is perhaps surprising that neither injury severity or corpus callosum lesions were predictive of pragmatic language outcomes at 24-months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…5,34 Previous research suggests that social disadvantage, including lower family income and lower levels of parental education, is associated with poorer outcomes after TBI. [38][39][40] Disadvantaged youth may lack access to treatment 30 and may have greater difficulty adhering to treatment when available. 40 The current intervention addressed many barriers to care by delivering care within the home at times convenient for the family.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing processes of myelination and synaptic pruning throughout adolescence and early adulthood coincide with increasing functional specificity of neural networks that support cognitive functioning (Asato, Terwilliger, Woo, & Luna, 2010;Hwang, Velanova, & Luna, 2010). Multiple studies have reported disruptions in these neural processes following diffuse axonal injury (DAI), which results from shearing of white matter-connecting pathways within neural networks associated with cognitive flexibility and inhibition Berryhill et al, 1995;Kinnunen et al, 2010;Levin et al, 2004;Ryan et al, 2014;Tasker, 2006). Perhaps not surprisingly, these childhood injuries are associated with widespread morphological changes, including reductions in cortical gray and white matter, as well as overall reductions in brain volume (Beauchamp, & Ditchfield, et al, 2011;Benson et al, 2007;Bigler, 2001Bigler, , 2007Ding et al, 2008;Gale, Baxter, Roundy, & Johnson, 2005;Trivedi et al, 2007;Wilde et al, 2005).…”
Section: Significancementioning
confidence: 99%